Synthesis and Characterization of NickelâCobalt Oxide (NiCo2O4) for Promising Supercapacitor Material - Puspitasari, P. (Springer Science and Business Media B.V., 2021)
Supercapacitor takes advantage of the broad electrode surface and thin dielectric material to reach higher capacity compared to the conventional capacitor. These factors make it possible for the supercapacitor to have larger energy density compared to the conventional and larger power density compared to a battery. Thus, supercapacitor would become a right solution as an energy storage device. NiCo2O4 is a good oxide material and exciting to learn due to its promising material and good electronic conductivity. NiCo2O4 was synthesised using self-combustion method then sintered at 400, 500, 600Â Â°C in time variations of 60, 120, 180Â min before testing with the XRD, SEM-EDAX, and VSM tests. The XRD test results showed a single-phase because of the appearance of crystallite in all samples in all temperature variations. The crystallite size, then, was calculated using the Scherrer equation. The results were: sample with 60Â min sintering duration had 6.699Â nm crystallite size, the sample with 120Â min sintering duration had 4.678Â nm crystallite size, and sample with 180Â min sintering duration had 5.883Â nm crystallite size. The morphology in the SEM test displayed the particles in small and nano size. The magnetic property test showed that the samples were superparamagnetic with the highest coercivity and retentivity was found in the sample of 500Â Â°C temperature and 60Â min sintering process. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.